Ο ANTONI RUBIÓ I LLUCH ΚΑΙ ΤΟ ΙΝΣΤΙΤΟΥΤΟ ΚΑΤΑΛΑΝΙΚΩΝ ΣΠΟΥΔΩΝ - BALCELLS, ALBERT (Eoa kai Esperia, 2007)
Antoni Rubió i Lluch (1856-1937), the well-known Catalan scholar anddiplomat, became Professor of Literature in the University of Barcelona in1885 and President of the Institute of Catalan Studies in 1907. He devoted hislife in promoting Catalan studies and with his work he enlightened the periodof Catalan history and civilization in 14th century Greece. He has publishedmany books and articles on that subject and especially the publication ofdocuments concerning the Catalan Duchy of Athens [Diplomatari del'OrientCatalà (1301-1409), Barcelona 1947] is valuable. As President of the Instituteof Catalan Studies he succeeded in promoting the Catalan as official languagein Spain and abroad.